A simple method to deduce minimal cut sets by tracing minimal paths for reliability assessment of power systems - Abdul Wahab, Noor Izzri; Kadhem, Athraa Ali (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper represents a simple method to deduce minimal cut sets by follow failure path from fault tree graphic for reliability assessment of power systems. This method uses the incidence matrix and logic for any numbers of flow paths from the power sources to the loads. The proposed matrix can be representing as the input data to any the computer program (or simulation). The results show that, the proposed method to deduce minimal cut sets from fault tree graphic to estimate reliability and safety of power systems is can be applicable in systems is more interconnected. An illustrative example, use RBTs shows the detail and characteristics of the proposed method.